2013
DOI: 10.1117/1.jei.22.1.013031
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary adaptive eye tracking for low-cost human computer interaction applications

Abstract: We present an evolutionary adaptive eye-tracking framework aiming for low-cost human computer interaction. The main focus is to guarantee eye-tracking performance without using high-cost devices and strongly controlled situations. The performance optimization of eye tracking is formulated into the dynamic control problem of deciding on an eye tracking algorithm structure and associated thresholds/parameters, where the dynamic control space is denoted by genotype and phenotype spaces. The evolutionary algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The MDP model needs to justify the use of the RL approach for adaptive tracking optimization as the events of consecutive trials for deciding the MDP state observed in discrete time space. The RL approach relying on the Markov assumption is very useful in solving many real-world problems by approximating system behaviors and has been successfully applied [37]. The MDP formulized for adaptive visual tracking also relies on the assumption of the Markov property.…”
Section: Mdp For Optimal Visual Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDP model needs to justify the use of the RL approach for adaptive tracking optimization as the events of consecutive trials for deciding the MDP state observed in discrete time space. The RL approach relying on the Markov assumption is very useful in solving many real-world problems by approximating system behaviors and has been successfully applied [37]. The MDP formulized for adaptive visual tracking also relies on the assumption of the Markov property.…”
Section: Mdp For Optimal Visual Trackingmentioning
confidence: 99%
“…Tracking performance was evaluated using recall, precision, and harmonic mean [37]. Given an N image frame sequence in a video denoted as V = (I 1 , I 2 , …, I N ), the bounding box sequence of the ground truth object was compared with that of a tracked object.…”
Section: Performance Measurementioning
confidence: 99%
“…Their Euclidean distance of feature descriptor is less than 0.001 (the feature descriptors have been normalized into [0,1]). Their positions are (4,4) and (10,9) in ROI. ROI is divided into 16 × 16 grids.…”
Section: Performance Comparison Among Vq Svq Sc and Llcmentioning
confidence: 99%
“…[4][5][6] However, it still remains a challenging problem because of some factors such as camera motion, cluttered background, occlusion, and varied object appearance. Building a discriminative representation for actions in videos is still challenging for better recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the tracking is performed by the partial Hough transform (PHT) and Kalman filter (KF). The more details can be found in [17] Let BN X be a parameter generator The interval of the threshold pivots between adjacent bit vector,…”
Section: The Genotype and Phenotype Leaning 41 Genotype Evolutionmentioning
confidence: 99%